Meningkatkan kemampuan penalaran matematis siswa madrasah tsanawiyah melalui penerapan model pembelajaran kooperatif tipe think pair share - Ike Natalliasari (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2015)
This research is an experimental study with a quantitative approach to analyse of the students reasoning ability through the application of cooperative learning model TPS. The population in this study were all students of islamic junior high schools (MTs) at the intermediate level of the 2012/2013 academic years in Tasikmalaya. The sample of this study were all students of MTs Nurul Falah taken randomly, and class VIII-B was chosen consisted of 35 students as experimental class and class VIII-C as control class. The instrument used in this study was included the ability of mathematical reasoning test. The analysis of the data used two different average test and ANOVA test using two lines of General Linear Model Univariate Analysis. Based on the results of this study, it has been found that (1) The improvement of reasoning ability and problem-solving ability of students who learned mathematic using cooperative model is better than those who learn mathematic using conventional model, (2) there are improvement differencies of reasoning ability and mathematical problem solving between the students who learn mathematic using cooperative learning model TPS type and students who learn mathematic using conventional model in terms of high-level capabilities, medium, and low, and (3) there is an interaction between learning and mathematical prior knowledge of students group (high, medium, low) in reasoning ability.